2018
DOI: 10.17576/jkukm-2018-30(2)-05
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sodium Sulfate and Sodium Chloride for Sonochemical Degradation on 1,4-benzoquinone and Hydroquinone in Aqueous Solution

Abstract: 1,4-benzoquinone, with the molecular formula C 6 H 4 O 2 , is generally known as a para-quinone. It is a six-member ring compound with an oxidized derivative known as 1,4-hydroquinone, which is a bright yellow crystal that has an irritating odour. On the other hand, hydroquinone, also known as benzene-1,4-diol, has the chemical formula C 6 H 4 (OH) 2. It looks like a white granular solid. Quinone is generally used as a precursor to hydroquinone. The skeletal muscle relaxant, ganglion blocking agent, benzoquino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…As multiple previous experimental studies on phenol derivates investigated, different molecules behave differently when water matrix components are added to sonolytic degradation experiments. For example, Uddin and Okitsu showed in their study, that the addition of sodium chloride had no effect on the sonolytic degradation of hydroquinone, whereas the decomposition of 1,4-benzoquinone was affected negatively by the presence of NaCl [16]. Another study by Xiao et al showed the different effect of added radical scavengers on ciprofloxacin and ibuprofen [17].…”
Section: Introductionmentioning
confidence: 98%
“…As multiple previous experimental studies on phenol derivates investigated, different molecules behave differently when water matrix components are added to sonolytic degradation experiments. For example, Uddin and Okitsu showed in their study, that the addition of sodium chloride had no effect on the sonolytic degradation of hydroquinone, whereas the decomposition of 1,4-benzoquinone was affected negatively by the presence of NaCl [16]. Another study by Xiao et al showed the different effect of added radical scavengers on ciprofloxacin and ibuprofen [17].…”
Section: Introductionmentioning
confidence: 98%